Experimental Evaluation of the Effects of SRP Reinforcement on the Flexural Behavior of CLT Panels - Giovanna Concu; Daniel Meloni; Monica Valdes (Technologies)
Cross-laminated timber (CLT) is a high-performance engineered timber that is very widely adopted. In several conditions, such as strength improvement at vulnerable connection points, local stress concentrations, existing structure retrofitting, and others, it is desirable to enhance the mechanical performance of CLT by applying additional reinforcement systems. This paper reports on an experimental campaign aimed at assessing the mechanical behavior of CLT panels reinforced with steel-reinforced polymers (SRPs). Twenty Sardinian Maritime Pine CLT panels, including unreinforced, SRP single- and double-layer reinforced panels, have been subjected to bending tests to determine the bending strength, stiffness, failure mechanism and enhancement of the reinforced panels compared to the unreinforced ones. In addition, an analytical model has been proposed to understand the mechanical behavior of SRP-reinforced CLT panels. The results show that SRP reinforcement significantly increases the strength and stiffness and influences the failure mechanism of CLT panels. The strength improvement induced by the reinforcement, however, is not proportional to its amount, since the increase due to the SRP double layer is only slightly higher than that due to the SRP single layer. The stiffness enhancement is less relevant, as expected. Attention has been paid to the possible shear failures of reinforced panels.